Esterification of Acetic Acid and Isobutanol in a Pervaporation Membrane Reactor Using Different Membranes - Korkmaz, Sevinc; Salt, Yavuz; Dincer, Salih (AMER CHEMICAL SOC, 2011)
In this study the ester-permeable polydimethylsiloxane (PDMS) and the water-permeable poly(vinyl alcohol) membranes prepared in our laboratory and the commercial Nafion 117, PERVAP 1201, and PERVAP 2216 membranes were used in the esterification of acetic acid with isobutanol catalyzed by Dowex 50W-X8 in a pervaporation membrane reactor process in order to shift the equilibrium by removal of relevant product from the reaction mixture. The effects of membrane type, the ratio of membrane area to reaction volume, and temperature were investigated. PERVAP 1201 membranes provided a higher water flux and higher selectivity than other hydrophilic membranes, but the highest fluxes were obtained using PDMS membrane, which selectively permeated isobutyl acetate compared to the other components. Increase in temperature and ratio of membrane area to reaction volume increased the conversion.
Keywords: SEPARATION; ACETATE; EQUILIBRIUM; ALCOHOL; NAFION-117; TRANSPORT; KINETICS; ETHANOL; WATER; Engineering